If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + 13 + -8b = -13 + -14b Combine like terms: 16 + 13 = 29 29 + -8b = -13 + -14b Solving 29 + -8b = -13 + -14b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '14b' to each side of the equation. 29 + -8b + 14b = -13 + -14b + 14b Combine like terms: -8b + 14b = 6b 29 + 6b = -13 + -14b + 14b Combine like terms: -14b + 14b = 0 29 + 6b = -13 + 0 29 + 6b = -13 Add '-29' to each side of the equation. 29 + -29 + 6b = -13 + -29 Combine like terms: 29 + -29 = 0 0 + 6b = -13 + -29 6b = -13 + -29 Combine like terms: -13 + -29 = -42 6b = -42 Divide each side by '6'. b = -7 Simplifying b = -7
| t^2-7tx-30x^2= | | 45+4x=-46-3 | | -x+6y=-28 | | -15.02-9.3c-11.98=-4.3c+17.5 | | -5-10p=-10p-3 | | 4x-9=-45 | | y=0x^2-1.3x+7 | | -4x+10y=-28 | | 1n+2n-4n=20 | | 48n^3=147a | | 48n^2=147n | | 2(x+4)+8=2(-x+12) | | 900/675×9 | | 2x/2=36°/2 | | h=16t^2+50t+50 | | 6-2x/3=1-x | | log[3]3x+log[3]4=log[3]36 | | 9v^2-2v-15=0 | | -7x+3(x+5)=-8x-9 | | 3(w+4)-5w=32 | | 30-2x=12+4x | | 3(x-1)+4=25 | | (8x-9)-(7x-9)= | | 5(5p-5)+7p=167 | | C=0.10x+7 | | 56m^2+376m+240=0 | | 6x+30=4x-6 | | 6x=d+2 | | 1=7-4/5x/5x | | x/(0.3-x)=5 | | 9(x+5)=36 | | 1/5d=7-4/x |